Cognitive Bias Terhadap Keputusan Investasi Saham: Literasi Keuangan Sebagai Moderasi - Sukhesy Eka Putri; Wendy; Helma Malini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research analyzes the influence of the relationship between Cognitive Bias on Investment Decisions which is moderated by Financial Literacy. Data was collected through a questionnaire and analyzed using Smart PLS version 3.2.9 which consists of testing the outer model and inner model. Sampling used purposive sampling, where respondents had investment experience of 1 year, ages ranging from 20 years to 43 years. This research produced 200 respondents who met the criteria. Representative, availability and anchoring have a significant positive influence on investment decisions. Likewise, financial literacy as moderation has a positive influence on investment decisions. However, financial literacy as moderation does not, namely weakening the relationship between representative, availability and anchoring.